The Role of Criminal Sanctions in Combating Minor Theft Crimes - Amalia Tasya (PT. Anagata Sembagi Education, 2024)
Petty theft is a form of crime that often occurs in everyday life and has the potential to cause social unrest. In the context of positive Indonesian law, petty theft is regulated in Article 364 of the Criminal Code which provides limits on the value of goods and forms of criminal sanctions. This article aims to analyze the effectiveness of criminal sanctions in overcoming petty theft and to examine the reality of law enforcement in the field. Through a normative and empirical legal approach, this study found that the application of criminal sanctions for petty theft often faces obstacles to effectiveness, especially in terms of the burden on the court, the condition of the perpetrator, and considerations of the values ​​of justice and benefit. Strengthening alternative case resolutions, such as restorative justice, is needed in an effort to create a more proportional and humane criminal system.